Digital Financial Literacy: Training for Woman Enterpreneurs in Managing Online Transaction - Saida Zainurossalamia ZA; Lusiana Desy Ariswati; Margareth Henrika; Ellen D. Oktanti Irianto; Rohana Nur Aini Aini (PT. Global Research Collaboration, 2025)
Digital financial literacy is an important skill for micro-entrepreneurs in dealing with the development of financial technology. However, many women entrepreneurs in the Samarinda City Joint Business Group (KUBe) still have a limited understanding of online transactions, digital financial recording, and security in using financial applications. This service program aims to improve digital financial literacy for five women entrepreneurs in KUBe through hands-on practice-based training and mentoring. The method used is participatory action research, which consists of four main stages: problem identification, training implementation, mentoring, and evaluation of results. The results of the service showed a significant improvement in various aspects of digital financial literacy. Participants' understanding of financial literacy increased by 68%, while skills in using digital payment applications increased by 122%. Awareness of online transaction security also increased by 115%, and business financial records increased by 86%. This increase shows that hands-on training is effective in improving participants' skills in managing digital transactions. The sustainability of this program is realized by the formation of a digital community to support participants in applying financial technology consistently. The results of this service are expected to be a model for other women's business groups in increasing economic independence through the use of digital financial technology. With increased digital financial literacy, women entrepreneurs can optimize online transactions, expand markets, and improve their economic welfare.